2021
DOI: 10.1111/age.13052
|View full text |Cite
|
Sign up to set email alerts
|

Gene mapping reveals the association between tyrosine protein kinase Abl1 and the silk yield of Bombyxmori

Abstract: The Z chromosome of the silkworm contains a major gene that influences silk yield. This major locus on chromosome Z accounts for 35.10% of the phenotypic variance. The location and identification of the gene have been a focus of silkworm genetics research. Unfortunately, identification of this gene has been difficult. We used extreme phenotype subpopulations and selected from a backcross population, BC 1 M, which was obtained using the high-yield strain 872B and the low-yield strain IS-Dazao as parents, for ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The proteins involved in these BP terms included SH3, multiple ankyrin repeat domains protein 3 and tyrosine-protein kinase ABL1 (see Table S2 ). The function of these proteins is mainly related to nerve development, cell division and growth ( Kim et al, 2020 ; Luan et al, 2021 ). Together, our results indicated that the physiological processes involved in the low temperature tolerance acted differently in the two tilapias.…”
Section: Discussionmentioning
confidence: 99%
“…The proteins involved in these BP terms included SH3, multiple ankyrin repeat domains protein 3 and tyrosine-protein kinase ABL1 (see Table S2 ). The function of these proteins is mainly related to nerve development, cell division and growth ( Kim et al, 2020 ; Luan et al, 2021 ). Together, our results indicated that the physiological processes involved in the low temperature tolerance acted differently in the two tilapias.…”
Section: Discussionmentioning
confidence: 99%
“…BmAbl1 is one of the potential targets in candidate regions. A recent report suggested that BmAbl1 had a strong correlation with cocoon shell weight [9,10]. However, how BmAbl1 affects the synthesis of silk protein is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Insects 2022, 13, 967 2 of 13 Within this QTL region, the tyrosine protein kinase, BmAbl1, is considered a potential target gene affecting CSW [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In the previous work, our research group used linkage analysis to circumvent the effects of gender in order to locate a quantitative trait loci (QTL) at 0-134k of the 1st chromosome (Chr1) and found that BmAbl1 (BMgn002070) was signi cantly related to the CSW in this region [11]. In the course of this research, we preliminarily found that the mapping region seemed to have been selected as a whole unit.…”
Section: Introductionmentioning
confidence: 98%
“…However, because the silkworm has complex genetic characteristics such as female complete linkage and other factors that could affect yield-related indicators, it is di cult to formulate suitable mapping materials and methods in forward genetic studies, making it di cult to research the genetic basis of silk yield. Therefore, over the past 100 years, only a few major genes have been detected, including BmGlcNase1 and BmAbl1 [11,12]. Since the inheritance of silk yield traits is dominated by additive effects [13] and the few identi ed genes have limited effects on molecular breeding, it is necessary to identify additional silk yield controlling genes.…”
Section: Introductionmentioning
confidence: 99%